REALIZATION OF THE PRODUCT AND SHARE OF THE ELECTRIC SIGNALS - MILLY, Miron (Trends in education, 2010)
The paper deals with some ways of realization the multiplication operation of two electric signals, using various types of analog multipliers, and realization the division operation of these signals, with application the analog multiplier, that is connected in the circuit feedback of the operation amplifier (OA).
Keywords: analog multiplier; divider; product; share; signal; operation amplifier; feedback.